1977
DOI: 10.1152/ajpregu.1977.232.3.r124
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and fetal osmoregulation: water transport across isolated human amnion

Abstract: The addition of human or ovine prolactin to the fetal side of the human amnion is associated with a latent decrease in membrane permeability. The specificity of this effect of prolactin is observed when equimolar concentrations of human placental lactogen and human growth hormone were used in place of ovine prolactin and failed to influence water transport. Likewise, the extracellular transport of p-aminohippurate across human amnion was unaffected by the addition of ovine prolactin. Tritiated water transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Osmoregulatory effect of prolactin have also been found in the chick embryo (Doneen and Smith 1982 ;Murphy et al 1986), and in the transport of water across the human amnion (Leontic and Tyson 1977 ;Leontic et al 1979). The increased speed of embryonic development with prolactin reported here may be related to the same osmoregulatory effect.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Osmoregulatory effect of prolactin have also been found in the chick embryo (Doneen and Smith 1982 ;Murphy et al 1986), and in the transport of water across the human amnion (Leontic and Tyson 1977 ;Leontic et al 1979). The increased speed of embryonic development with prolactin reported here may be related to the same osmoregulatory effect.…”
Section: Discussionsupporting
confidence: 73%
“…Reports on the role of prolactin during early embryonic development are rare but since it is known that prolactin is secreted from the endometrium (Maslar and Riddick 1979), it is reasonable to postulate the presence of a direct action on the embryo which may influence its development. Since prolactin has an osmoregulatory function in the amniotic fluid (Leontic and Tyson 1977), it may have a similar action on the early stage of the mammalian embryo, which would be indicated by changes in the rate of development in the presence of prolactin. This report deals with the in vitro effects of prolactin doses on mouse embryos.…”
mentioning
confidence: 99%
“…The PRL used for these studies is known to be contaminated with minimal amounts of AVP; however Leontic and Tyson (7) have shown that AVP in concentrations far exceeding those contaminating ovine PRL preparations does not affect water transport (6).…”
Section: Resultsmentioning
confidence: 99%
“…There are structural similarities between the choroid plexus and the amniotic mem brane [10], Prolactin stimulates fluid trans port across the amniotic membrane [11,13], while cortisol inhibitis it [13], Cortisol also reduces CSF production [10], There are no studies which specifically examine the effects of prolactin on CSF production. It is possible that part of the increased brain water in treated animals is due to an increase in CSF production mediated by prolactin.…”
Section: Discussionmentioning
confidence: 99%